The Environmental Quality Act 1974: a significant legal instrument for implementing environmental policy directives of Malaysia - Mustafa, Maizatun (International Islamic University Malaysia, 2011)
In Malaysia, the Environmental Quality Act 1974 is considered to be the most comprehensive piece of legislation promulgated to deal with environmental protection and pollution control. The Act also forms the basic instrument for achieving environmental policy objectives. As a developing country that strives for economic growth, Malaysia's rapid development activities especially since the early 1980s have unveiled new dimensions to environmental concerns. Since its introduction more than 30 years ago, the scope and strategies of this Act have been constantly amended, altered or improved in the pursuit of environmental policy objectives. Thus, in the context of environmental protection, the Environmental Quality Act 1974 needs to be pro-active and flexible enough to accommodate new measures for facing challenging environmental problems. These changes provide an indication of the increasing complexities of environmental issues facing Malaysia. This paper examines the development of environmental strategies that has taken place within the framework of the Act, based on Malaysia's environmental policy directives particularly on sustainable development.